The Translation of Onomatopoeia in Ariel Duyung’s Comic (Good/Bad Fortune) - Yuria, Hersa; Ardi, Havid (English Language and Literature, 2024)
Several aims have been established, including the examination of onomatopoeia types and the technique employed for translating onomatopoeia in the webtoon comic titled "Good/Bad Fortune" by Ariel Duyung.The research employs a descriptive qualitative method, and the data for this study is divided into two parts. The first set of data comprises onomatopoeic words found in the original version of the comic "Good/Bad Fortune," while the second set consists of the English translation version. In total, there are 62 instances of data. Moreover, six translation techniques are employed for translating onomatopoeia, with the following distribution: 27 (43.5%) cases of establishing equivalents, 27 (43.5%) cases of borrowing, 3 (4.8%) cases of adaptation, 1 (1.6%) case of modulation, 3 (4.8%) cases of discursive creation, and 1 (1.6%) case of substitution.